2008
DOI: 10.1016/j.aquaculture.2008.06.016
|View full text |Cite
|
Sign up to set email alerts
|

A flow-through rearing system for ecophysiological studies of Pacific oyster Crassostrea gigas larvae

Abstract: While literature is relatively abundant on adult shellfish, ecophysiological studies at the larval stage are scarce because of both technical difficulties and inadequate methodology. A tool dedicated to provide basic information for larval ecophysiology was accordingly developed. Two steps were followed: first a flow-through method of Crassostrea gigas larval culture was perfected during a set of experiments in which rearing systems and larval density were assessed. Then a continuous hydrobiological data recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 23 publications
1
59
1
Order By: Relevance
“…Once the oysters were reproductively mature, gametes from 30 individuals (1/3 males, 2/3 females), obtained by stripping, were mixed in a 5 l jar at 50 spermatozoids per oocyte. The fertilized oocytes completed their embryonic development in 150 l tanks filled with 1 µm filtered and UV-treated seawater at 21°C for 24 h. The D-larvae were then collected and reared in flow-through rearing systems at 25°C (Rico-Villa et al 2008). At the end of the pelagic phase (12 d), competent larvae were collected on a 225 µm sieve and allowed to settle on cultch.…”
Section: Animalsmentioning
confidence: 99%
“…Once the oysters were reproductively mature, gametes from 30 individuals (1/3 males, 2/3 females), obtained by stripping, were mixed in a 5 l jar at 50 spermatozoids per oocyte. The fertilized oocytes completed their embryonic development in 150 l tanks filled with 1 µm filtered and UV-treated seawater at 21°C for 24 h. The D-larvae were then collected and reared in flow-through rearing systems at 25°C (Rico-Villa et al 2008). At the end of the pelagic phase (12 d), competent larvae were collected on a 225 µm sieve and allowed to settle on cultch.…”
Section: Animalsmentioning
confidence: 99%
“…Sarkis et al (2006) showed that calico scallop growth for FT-reared larvae was comparable or significantly higher than in the static system, which corroborate with our findings. Similarly, Rico-Villa et al (2008) reported significant growth and competence improvements in Crassostria gigas larvae reared in the flow-through system compared to static system. These authors also revealed that the use of FTS with constant flows of highquality water and a daily cleaning of the sieve clogs facilitated the circulation in the rearing tank and removal of metabolic waste products providing favorable conditions for larval development.…”
Section: Discussionmentioning
confidence: 99%
“…These authors also revealed that the use of FTS with constant flows of highquality water and a daily cleaning of the sieve clogs facilitated the circulation in the rearing tank and removal of metabolic waste products providing favorable conditions for larval development. Several studies suggested an association between the stocking density and the water exchange rate (Magnesen et al 2006;Rico-Villa et al 2008). Furthermore, Andersen et al (2000) and Sarkis et al (2006) reported a reduction in growth performance at high stocking density when they reared scallop (Pecten maximus) and oyster (C. gigas) larvae in FTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twentyfour hours later, the incubator tank was drained onto a 35 µm sieve and D-shaped larvae were concentrated in a 5 L graduated cylinder. D-shaped larvae were counted (3 × 20 µl) and then reared in a through-flow culture system (Magnesen et al 2006;Rico-Villa et al 2008;Sarkis et al 2006) in 4 replicates. D-shaped larvae were fed using three tropical species of micro-algae: Isochrysis clone T-Iso, Chaetoceros minus and Chaetoceros gracilis.…”
Section: Demonstration Of Hatchery Applicationmentioning
confidence: 99%